2016
DOI: 10.1161/circgenetics.115.001190
|View full text |Cite
|
Sign up to set email alerts
|

International Genome-Wide Association Study Consortium Identifies Novel Loci Associated With Blood Pressure in Children and Adolescents

Abstract: 266S ystolic and diastolic blood pressure (SBP and DBP) are complex phenotypes, with known environmental and genetic risk factors.1 Elevated SBP and DBP are associated with premature mortality 2,3 and cardiovascular diseases. 2,4-9 Clinical Perspective on p 278Recent genome-wide association studies (GWAS) have identified genetic variants associated with adult SBP and DBP and hypertension. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Several of these loci are in biologically plausible candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 84 publications
2
41
0
Order By: Relevance
“…Of the 389 SNPs (Adeyemo et al, 2009;Cho et al, 2009;Ehret et al, 2016;International Consortium for Blood Pressure Genome-Wide Association Studies et al, 2011;Evangelou et al, 2018;Fox et al, 2011;Franceschini et al, 2013;Ganesh et al, 2014Ganesh et al, , 2013Ho et al, 2011;Hoffmann et al, 2017;Johnson, Newton-Cheh, et al, 2011;Johnson, Gaunt, et al, 2011;Kato et al, 2015Kato et al, , 2011Kidambi et al, 2012;Levy et al, 2009;Li et al, 2017;Liang et al, 2017;Liu et al, 2016;Newton-Cheh, Johnson, et al, 2009;Newton-Cheh, Larson, et al, 2009;Parmar et al, 2016;Simino et al, 2014;Surendran et al, 2016;Takeuchi et al, 2010;Tragante et al, 2014;Wain et al, 2017Wain et al, , 2011Warren et al, 2017) identified for replication, 330 (85%) SNPs were included in the replication analysis. Fifty-nine SNPs that were either rare (<0.01) or poorly imputed (INFO score <0.3) in the EMaBS sample were not included in the replication analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 389 SNPs (Adeyemo et al, 2009;Cho et al, 2009;Ehret et al, 2016;International Consortium for Blood Pressure Genome-Wide Association Studies et al, 2011;Evangelou et al, 2018;Fox et al, 2011;Franceschini et al, 2013;Ganesh et al, 2014Ganesh et al, , 2013Ho et al, 2011;Hoffmann et al, 2017;Johnson, Newton-Cheh, et al, 2011;Johnson, Gaunt, et al, 2011;Kato et al, 2015Kato et al, , 2011Kidambi et al, 2012;Levy et al, 2009;Li et al, 2017;Liang et al, 2017;Liu et al, 2016;Newton-Cheh, Johnson, et al, 2009;Newton-Cheh, Larson, et al, 2009;Parmar et al, 2016;Simino et al, 2014;Surendran et al, 2016;Takeuchi et al, 2010;Tragante et al, 2014;Wain et al, 2017Wain et al, , 2011Warren et al, 2017) identified for replication, 330 (85%) SNPs were included in the replication analysis. Fifty-nine SNPs that were either rare (<0.01) or poorly imputed (INFO score <0.3) in the EMaBS sample were not included in the replication analysis.…”
Section: Resultsmentioning
confidence: 99%
“…An international GWAS identified ITPR1 between the novel loci associated with blood pressure in children and adolescents [110]. Finally, in the Hispanic population, ITPR1 was associated to the pathophysiology of childhood obesity [96], while ITPR3 was linked to body mass index variants conferring a high risk of extreme obesity [94].…”
Section: Potential Role Of Itprs In Human Disease: Evidence From Gwasmentioning
confidence: 99%
“…Variants in this gene have been identified in individuals with carotid body tumors and pheochromocytomas/paragangliomas, endocrine tumors that secrete dopamine and/or norepinephrine and can modulate BP regulation even when tumors are not clinically apparent (73,74). Variants near this locus have been marginally associated with DBP in pre-pubertal European children (75). Tyrosinase (with its related protein, TYRP1) catalyzes the first rate-limiting step in pathway in the formation of L-Dopa (76).…”
Section: Biological Relevance Of Newly Identified Bp Locimentioning
confidence: 99%